Care Needs, Organisational Instances and Bio-political Power: The Royal Hospital of San Giacomo degli Spagnoli of Palermo in the Seventeenth Century - Roberto Rossi (The Journal of European Economic History (JEEH), 2025)
Care structures in the modern age have undergone profound transformations due to the changed operating environment and advances in medical technology. However, according to Foucault's theory, the advances in medical treatment and care organization are considered as part of a power system and should be examined as a government technology tool. In this sense, the military hospitals were an important part of this social management organization. The case of the Royal Hospital of San Giacomo degli Spagnoli in Palermo represents a significant case to analyse the processes of organisational and functional transformation that affected hospital structures in the second half of the 17th century within a bio-political context.
Keywords: 330